1998
DOI: 10.1001/jama.279.20.1629
|View full text |Cite
|
Sign up to set email alerts
|

Nebulized Budesonide and Oral Dexamethasone for Treatment of Croup

Abstract: Context.-The effectiveness of glucocorticoids for patients with croup is well established but it remains uncertain which glucocorticoid regimen is most effective. Objective.-To determine the effectiveness of 3 glucocorticoid regimens in patients with croup. Design.-Randomized controlled trial with parallel design. Setting.-Emergency departments of 2 Canadian pediatric tertiary care hospitals. Participants.-Children with a clinical syndrome consistent with croup, aged 3 months to 5 years, with a croup score of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(17 citation statements)
references
References 21 publications
1
14
0
2
Order By: Relevance
“…However, they found no statistically significant difference between oral dexamethasone and nebulized budesonide compatible with our results. In another study, nebulized budesonide, oral dexamethasone and a combination of these were given to the patients with croup, but no statistically significant difference was found among the groups [16]. It was suggested that oral dexamethasone could be used in day care settings, emergency departments, and office practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, they found no statistically significant difference between oral dexamethasone and nebulized budesonide compatible with our results. In another study, nebulized budesonide, oral dexamethasone and a combination of these were given to the patients with croup, but no statistically significant difference was found among the groups [16]. It was suggested that oral dexamethasone could be used in day care settings, emergency departments, and office practice.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, glucocorticoids are generally considered to have broad-reaching anti-inflammatory properties and in fact have been the focus of several clinical hRSV trials. Unfortunately, these trials suggest that when used alone in the absence of antivirals, glucocorticoid treatment has only marginal, if any, benefit in the treatment of hRSV-infection and its associated inflammatory response (72,83,84,212,213,231,307,331,334,338,365). A meta-analysis of several these studies demonstrated that systemic glucocorticoids reduced the total length of hospital stay by only 0.43 day per patient, an effect reduced to only 0.29 day per patient when patients with previous episodes of wheezing were excluded from the analysis (137), a statistically significant difference with overall minor clinical impact.…”
Section: Therapy For Hrsv Diseasementioning
confidence: 99%
“…The effectiveness of oral or intramuscular dexamethasone (0.6 mg· kg -1 ) as a treatment for patients with moderate-to-severe croup is well established [2,[14][15][16]. Doses of dexamethasone ranging 0.15-0.6 mg· kg -1 have been shown to be similarly efficacious for treating moderate croup (table 5) [17].…”
Section: Treatmentmentioning
confidence: 99%